PENGARUH PENAMBAHAN TEPUNG KUNYIT (Curcuma domestica Valet) DALAM PAKAN PUYUH (Coturnix-coturnix Japonica) PEDAGING TERHADAP PERFORMANS, PROFIL DARAH, KANDUNGAN LEMAK DAN KOLESTEROL DAGING PUYUH - , ASTRIANA NAPIRAH, Dr. Ir. Supadmo, MS ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Turmeric (Curcuma domestica Valet) is one of the plant used as a growth promotor and immunomodulator on poultry. Turmeric contains curcumin, an active substance which is able to increase gastrointestinal activity, poultry immunity, and carcass quality of poultry. This experiment was helt to study the effect of turmeric as phytibiotic on performance, blood profile, fat and cholesterol meat of quail. One hundred and twenty eight quails were grouped into 4 treatments with 4 replications based on completely randomized design. Diet used contain 24% crude protein and 2900 kcal/kg metabolizable energy. The treatments were R0 (basal feed + 0.00% turmeric meal), R1 (basal feed + 0.10% turmeric meal), R2 (basal feed + 0.50% turmeric meal) and R3 (basal feed + 1.00% turmeric meal). Parameters measured were quail performance (include weight gain, feed consumption, and feed conversion ratio), blood profile (include erithrocyte, leucocyte and its diferential count, neutrophil : lymphocyte ratio, Hb, hematocrite and total plasma proteins), fat and cholesterol level of quail meat. Data obtained during 42 days experiment was analyzed using analysis of variance based on completely randomized design and continued using least significant difference test. Feed consumption, weight gain and feed conversion ratio of quails in turmeric-fed group did not differ significant (P>0.05) with control group. Feeding turmeric gave a significant effect on leucocyte, neutrophil, and lymphocyte count of quails. At 42 days of age, addition 1.00% of turmeric meal in quail feed, significantly (P<0.05) decreased neutrophil count, indicate antibacterial activity of curcumin contained in turmeric. Fat and cholesterol of quail meat between turmeric-fed group and control group were not differ significant (P>0.05). The result showed that applied turmeric meal up to 1.00% in quail feed did not give any negative effect on quail performance, did not decrease fat and cholesterol level of quail meat, but showed antibacterial activity by decrease neutrophil percentage of quail blood.